Translation and psychometric evaluation of the Persian version of the role model apperception tool (RoMAT) in undergraduate nursing students - Marzieh Azadian; Tahereh Nasrabadi; Abbas Ebadi; Jamileh Mokhtari Nouri (Journal of Medical Ethics and History of Medicine, 2022)
Role modeling is one of the most influential components of teaching professional behaviors to nursing students. The Role Model Apperception Tool (RoMAT) was designed in the Netherlands to measure role modeling behaviors in clinical educators. The aim of this study was assess the psychometrics of the Persian version of this tool.In a methodological study, the Persian version of the RoMAT tool was developed using the forward-backward translation method. Face validity was confirmed through cognitive interviews, and content validity was done by a panel of 12 experts. Construct validity was assessed through exploratory factor analysis (n = 200), and confirmatory factor analysis (n = 142) was evaluated after the tool was completed online by undergraduate nursing students. Reliability was confirmed using internal consistency and test and retest methods. Furthermore, ceiling and floor effects were assessed.The two components of "professional competencies" and "leadership competencies" emerged with a cumulative variance of 62.01%, a reliability with Cronbach's alpha of 0.93 and 0.83, and an intraclass correlation of 0.9 and 0.78, respectively. It was concluded that the Persian version of the Role Model Apperception Tool is a valid and reliable tool and can be used to investigate the role modeling behaviors of clinical instructors of nursing students.